The next chapter / Rebecca Ryan. - Ryan, Rebecca (Simon & Schuster, 2025)
Lily Brown prides herself on her organised, surprise-free life. Whether it's a charity yoga for polar bears or crafting a ninety-six-piece balloon arch, Lily always goes the extra mile. But when her adoptive father asks her to reconnect with her birth mother, Lola Starr - a legendary pop punk singer who vanished from fame - Lily decides to venture off the well-trodden path. With her best friend Seb, Lily tracks Lola to her humble hotel on the beautiful Isle of Skye in Scotland, far from the glamorous life she imagined. Hiding the truth, Lily gets to know Lola and finds a kind, free-spirited woman. If life wasn't complicated enough - she meets Noah, a charming travel writer on a quest to discover hidden gems. As Lily takes a chance and embraces new possibilities, she begins to question whether the safe rules she's built her life around are what she really needs.